“Always opening and never closing”: How dialogical therapists understand and create reflective conversations in network meetings - Sidis, A. E.; Moore, A.R.; Pickard, J.; Deane, F. P. (Frontiers in Psychology, 2022)
Tom Andersen’s reflecting team process, which allowed families to witness and respond to the talk of professionals during therapy sessions, has been described as revolutionary in the field of family therapy. Reflecting teams are prominent in a number of family therapy approaches, more recently in narrative and dialogical therapies. This way of working is considered more a philosophy than a technique, and has been received positively by both therapists and service users. This paper describes how dialogical therapists conceptualise the reflective process, how they work to engage families in reflective dialogues and to consider how this supports change. We conducted semi-structured, reflective interviews with 12 dialogical therapists with between 2 and 20 years of experience. Interpretative Phenomenological Analysis of transcribed interviews identified varying conceptualisations of the reflecting process and descriptions of therapist actions that support reflective talk among network members. We adopted a dialogical approach to interpretation of this data. In this sense, we did not aim to condense accounts into consensus but instead to describe variations and new ways of understanding dialogical reflecting team practices. Four themes were identified: Lived experience as expertise; Listening to the self and hearing others; Relational responsiveness and fostering connection; and Opening space for something new. We applied these themes to psychotherapy process literature both within family therapy literature and more broadly to understand more about how reflecting teams promote helpful and healing conversations in practice.